Latino poetry : the Library of America anthology - González, Rigoberto (Library of America, 2024)
This landmark Latinx poetry collection offers "a wondrous journey through the passions, the ideas, and the diversity of a people redefining what it means to be American" (Héctor Tobar, Pulitzer Prize winner) Includes more than 180 poets, spanning from the 17th century to today, and presents those poems written in Spanish in the original and in English translation.--